Negotiation of East–West identities in the German children’s literature Gertrude Grenzenlos - Naflah Fakhira Maulida; Lina Meilinawati Rahayu; Ida Farida Sachmadi (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
Since the 1960s, German children’s and young adult literature has placed strong emphasis on political aspects, presenting both historical and contemporary social depictions. A subgenre of problem-oriented children’s literature has even emerged, specifically focusing on more particular political issues such as social identity, ideology, and fascism. Regarding social identity, German children’s literature tends to highlight the history of the Holocaust and post-war trauma. However, there are still few works that address ideology-based social identity issues with a focus on social discrimination. Gertrude grenzenlos (2018) by Judith Burger presents a story of social discrimination experienced by a child protagonist in the East German community due to ideological differences. This study aims to show how this children’s novel portrays social discrimination channelled by the government as institutional discrimination both directly and indirectly, against families inclined toward Western ideology. The study employs identity theory by Tajfel and Turner along with Foucault's theory of power. Using a narratological approach, the narrative reveals the dynamics of power between communities of differing ideologies, which then form new identities and blur social boundaries because power is not absolute, thus creating ideological gaps that allow for the negotiation of power. Consequently, the novel illustrates the negotiation of Western and Eastern ideologies within the authoritarian and exclusive socio-political structure of East German society.   Sejak 1960-an, sastra anak dan remaja Jerman menekankan aspek politik, menyajikan gambaran sosial historis dan kontemporer di dalamnya. Sebuah subgenre sastra anak berorientasi masalah muncul menyoroti isu-isu seperti identitas sosial, konflik ideologi, dan fasisme. Dalam konteks identitas sosial, sastra anak Jerman kerap menyoroti sejarah Holocaust dan trauma pascaperang, namun karya yang membahas identitas berbasis ideologi dengan fokus pada diskriminasi sosial masih relatif sedikit. Kemudian, Gertrude grenzenlos (2018) karya Judith Burger terbit yang menceritakan diskriminasi sosial yang dialami seorang tokoh anak di komunitas Jerman Timur akibat perbedaan ideologis. Penelitian ini memperlihatkan bagaimana novel itu menggambarkan diskriminasi sosial yang disalurkan pemerintah sebagai bentuk diskriminasi institusional, baik secara langsung maupun tidak langsung, terhadap keluarga yang condong ke ideologi Barat. Kajian memakai teori identitas Tajfel dan Turner serta teori kekuasaan Foucault. Dengan pendekatan naratologis, narasi mengungkap dinamika kekuasaan antara komunitas berideologi berbeda yang membentuk identitas baru dan mengaburkan batas sosial karena kekuasaan tidak mutlak, sehingga tercipta celah ideologis yang memungkinkan negosiasi kekuasaan. Akibatnya, novel ini menggambarkan negosiasi antara ideologi Barat dan Timur dalam struktur sosial-politik Jerman Timur yang otoriter dan eksklusif. Kajian ini juga menyoroti dampak pengalaman individual terhadap solidaritas komunitas serta bagaimana praktik sehari-hari, kebijakan, dan wacana resmi saling berinteraksi sehingga memperkuat atau melemahkan posisi sosial kelompok yang menjadi korban diskriminasi. dalam konteks perubahan sejarah dan politik.